History, identity, art: visually expressing Nicodemus, Kansas' identity - Edwards, Leah (Kansas State University, 2014)
History is embedded in a landscape. History of a community is embedded in the landscape where land was inhabited, cultivated, and where people have and continue to thrive. Rural communities have this embedded history and culture to look back. However, these communities are suffering from loss of population, jobs, economic stability, and accessibility (Woods 2008). This phenomenon can destroy not only communities and peoples’ lives, but also the history and culture that is embedded in a landscape. Nicodemus, Kansas a rural communities with an important history. This history begins after the Civil War during times of new found freedom and the reality of independence for many former African-American slaves. The residents and descendants of Nicodemus are passionate and proud of their history and see their community identity as embedded in the history and culture. Nicodemus has experienced loss of population and economic vitality throughout its history. However, Nicodemans’ strong connection to the history remains intact. The study argues that art can provide a way of expressing Nicodemus, Kansas’s identity. This study is primarily an art-based investigation into what materials, mediums, and forms of art can best express the identity and history of Nicodemus, Kansas. Art-based research is less concerned with the discovery of truth than with the creation of meaning (Eisner 1981). “...[V]isual art is a significant source of information about the social world, including cultural aspects of social life” (Leavy 2009, 218). Research methods include historiography, literature review, oral history, reflexive critique and site visits, culminating in the creation of a series of mixed media artworks. Through the research and creation of artworks, the identity of Nicodemus, Kansas is expressed visually.
Keywords: History; Cultural landscape; Nicodemus; Kansas; Community identity; Art; Landscape Architecture (0390)